Migrant remittances in South Asia : social, economic and political implications - Rahman, Mizanur, 1972-; Tan, Tai Yong; Ullah, A. K. M. Ahsan (Basingstoke : Palgrave Macmillan, 2014)
Remittance is the most beneficial private transaction in the global economy. The South Asian region accounts for about one fourth of the global remittance flows destined for developing countries, contributing to over ten percent of the gross domestic product (GDP) of South Asia. This significant amount of remittance has enormous potential for development in the region. The volume, essentially a South Asian viewpoint, provides theoretical treatments of remittance and how its development potential is translated into reality. The authors meticulously delve into the diverse mechanisms through which migrant communities remit, investigating how recipients engage in the development process in South Asia.
Migrant Remittances in South Asia: An Introduction; Md Mizanur Rahman, Tan Tai Yong and AKM Ahsan Ullah -- PART I: REMITTANCE AND CONCEPTUAL ISSUES -- 1.Understanding Remittances: Theoretical and Methodological Issues; Md Mizanur Rahman and Lian Kwen Fee -- 2.Gender and Remittances: Remodelling Remittance Exposure; AKM Ahsan Ullah -- PART II: REMITTANCE TRANSFER SYSTEMS -- 3.Formal Remittances: Costs and efficiencies of remittance transfers to South Asia; Bhupal Singh -- 4.Social Organization of Hundi: Informal Remittance Transfers to South Asia; Md Mizanur Rahman and Brenda S.A. Yeoh -- PART III: IMPLICATIONS OF REMITTANCES IN SOUTH ASIA -- 5.The social dynamics of remittance-receiving in Pakistan: Agency and opportunity among non-migrants in a transnational social field; Marta Bivand Erdal -- 6.Remittances and SME Development: Reflections from South Asia; Rita Afsar -- 7.Gendering Remittances: Contested Masculinities among Bangladeshi Muslim Male Immigrants in New York City; Natacha Stevanovic-Fenn -- 8.Globalization of Remittances in India: Toward a Sociological Perspective; Vani S Kulkarni -- 9.When Money Follows the Corpse: Remittances of Deceased Migrants in South Asia; AKM Ahsan Ullah and Mallik Akram Hossain -- 10.Fertility Responses to Migrant Remittances in Pakistan; Mazhar Mughal an Amar Anwar -- 11.Migrants' Private Giving and Development in Central Gujarat, India; Puja Guha -- 12.Uses and Impacts of Remittances in Nepal; Bhubanesh Pant.
Includes bibliographical references and index.
Keywords: Economic development -- South Asia; Emigrant remittances -- South Asia